Implementation of cross correlation for energy discrimination on the time‐of‐flight spectrometer CORELLI. Issue 2 (30th March 2018) - Ye, Feng; Liu, Yaohua; Whitfield, Ross; Osborn, Ray; Rosenkranz, Stephan
Abstract : With implementation of the cross‐correlation technique at the short‐pulse Spallation Neutron Source (SNS), Oak Ridge, Tennessee, USA, CORELLI obtains both the total scattering and the elastic‐only scattering simultaneously from a single measurement with an unprecedented data collection rate. Abstract : The CORELLI instrument at Oak Ridge National Laboratory is a statistical chopper spectrometer designed and optimized to probe complex disorder in crystalline materials through diffuse scattering experiments. On CORELLI, the high efficiency of white‐beam Laue diffraction combined with elastic discrimination have enabled an unprecedented data collection rate to obtain both the total and the elastic‐only scattering over a large volume of reciprocal space from a single measurement. To achieve this, CORELLI is equipped with a statistical chopper to modulate the incoming neutron beam quasi‐randomly, and then the cross‐correlation method is applied to reconstruct the elastic component from the scattering data. Details of the implementation of the cross‐correlation method on CORELLI are given and its performance is discussed.